Analisis Upgrading pada Rantai Nilai Kopi Robusta di Kecamatan Kare Kabupaten Madiun Indonesia - Rumaisha Vinna Aulia; Sri Tjondro Winarno; Fatchur Rozci (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Robusta coffee ranks as a key commodity in the Kare District, significantly contributing to the area's economy. However, due to limited market access, farmers have yet to capitalize on the advantages of robusta coffee farming fully. This research aims to examine how different aspects of upgrading, namely product, process, channel, and functional upgrading, affect the value chain of Robusta coffee in the Kare Subdistrict. Data were collected from May to June 2025 through questionnaires, interviews, and a literature review, involving 50 farmers, one collector-trader, and 1 coffee processor, using purposive sampling. Respondents were selected based on their active participation and key roles in the coffee value chain, ensuring that the data reflect the practices and interactions of core actors. The analysis was conducted using SEM-PLS with WarpPLS version 8.0. The coffee value chain in Kare involves six actors: farmers, collectors, processors, coffee shops, retailers, and consumers, with interconnected relationships. This study examined the relationships among Product upgrading (0.930), process upgrading (0.959), functional upgrading (0.876), and channel upgrading (0.614). All variables demonstrate significant positive effects on the value chain (p < 0.001). These results suggest that, overall, an integrated upgrading strategy can enhance value addition, productivity, and farmers' welfare while strengthening the local competitiveness of Robusta coffee.